PARTICIPATORY ANALYSIS OF THE CONSTRAINTS TO ADOPTION AND DIFFUSION OF ARTIFICIALINSEMINATION IN DAIRYING IN LOWER ATBARA RIVER AREA (Journal of Veterinary Medicine and Animal Production, 2021)
The main objective of this study was to analyze the constraints to adoption and diffusion of Artificial Insemination (A.I.) as a new technology for improving indigenous cattle in Lower Atbra River Area as perceived by the cattle owners themselves. Data was collected using Participatory Rural Appraisal (PRA) approach from five villages of Lower Atbra River Area. A total of 70 cattle owners attended the meeting and the discussions were conducted with all the participant using different PRA tools. The PRA information was recorded on Flip charts. Mapping, time and trend lines, seasonal calendars, diagramming and ranking were used to elicit, record, analyze and agree on social and technical data. The results indicated that the most pressing constraint perceived by the cattle owners was lack of A.I. facilities while the least considered constraint was free range system of animal husbandry. The most important social factors stimulating the adoption of A.I. were personal communication network and social participation, while opposition in the farming community and social isolation were perceived as factors inhibiting adoption of A.I. technology. The most important psychological factors stimulating the adoption of A.I. technology were innovation proneness and risk taking, while complexity of A.I. technology and risk avoidance were perceived as important factors inhibiting the adoption of A.I. technology.
Keywords: PARTICIPATORY ANALYSIS; CONSTRAINTS